Zmiany w dochodach i akumulacji rolniczych gospodarstw rodzinnych w latach dziewięćdziesiątych w ujęciu przestrzennym - Wiatrak, Andrzej; Karbowiak, Katarzyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1997)
This paper presents analysis - made on the basis of the investigation covering 369 family farms - of changes in income and accumulation in family farms between 1989 and 1994. As it appears from an analysis, spatial differentiation of agricultural income deepened. Importance of non-agricultural incomes from other gainful activity also increased. Summing up, incomes of family farms were generally low, and in a consequence of this fact, the accumulation was insufficient (however, its level rose with the growing level of income) and even in some regions accumulation reached the negative level.